Emancipation, Women and the State: A Competing Agenda in the 20th Century Malaysia - Azhari, Che Husna (Intellectual Discourse, 2013)
The structural contradictions of being Muslim and members of a nation-state for women in modern-day Muslim nation-states created after the Second World War have never been fully resolved. The problem is even more compounded for Malaysia, which started life as a collection of sultanates, graduating to a multi-racial nation-state. In the beginning, Malay women saw emancipation as involvement in party politics. But much of the development envisaged for women was hampered by illiteracy. Since 1970, with the new found petro-ringgit, however, the situation changed. Women attained emancipation in mobility, political and economic spheres. Yet, an appropriate space for motherhood and wifehood has not been carved out in the industrial state.